Teknik Ngudari Reribed untuk Mengarahkan Meaning of life - Juwita Finayanti; Nur Hidayah; Adi Atmoko (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This research was aimed to explore ngudari reribed techniques that have been used to guide students' meaning of life. This study uses the Borg & Gall approach as a method. The technique of reribed itself is a mental counseling technique that aims to release all the problems of one's life. Through stages such as kandha-takon, weruh-ngerti-krasa-dewe, and saiki-kene-ngene-gnawing. If someone has been able to drive reribed, then his life will be doomed from envy and pride. In the end it will feel a happy life, and happiness itself is a factor in achieving someone's meaning of life.Abstrak: Penelitian ini bertujuan untuk mengeksplorasi teknik ngudari reribed untuk mengarahkan meaning of life siswa. Penelitian ini menggunakan pendekatan Borg & Gall sebagai metode. Teknik ngudari reribed sendiri merupakan salah satu teknik konseling kawruh jiwa yang tujuannya untuk melepas segala problema hidup seseorang. Melalui tahapan-tahapan seperti kandha-takon, weruh-ngerti-krasa-dewe, dan saiki-kene-ngene-gelem. Apabila seseorang telah mampu ngudari reribed, maka hidupnya akan terbebaas dari rasa iri dan sombong. Pada akhirnya akan merasakan hidup bahagia, dan bahagia itu sendiri adalah faktor tercapainya meaning of life seseorang.